2023
DOI: 10.1186/s13568-023-01520-3
|View full text |Cite
|
Sign up to set email alerts
|

The gut microbiota pathway mechanisms of diabetes

Abstract: The contribution of dysbiotic gut microbiota configuration is essential when making reference to the metabolic disorders by increasing energy. It is important to understand that the gut microbiota induced metabolic disease mechanisms and inflammations. Thus it is imperative to have an insight into the state of all chronic subclinical inflammations influencing disease outcomes. However, from the emerging studies, there still exist inconsistencies in the findings of such studies. While making the best out of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 80 publications
0
6
0
Order By: Relevance
“…The relative abundance of Firmicutes is positively correlated with insulin sensitivity [ 163 ]. Insulin resistance may result from chronic inflammation, during which pro-inflammatory factors (TNF-α, IL-6, and others) can phosphorylate the insulin receptor substrate, converting it into serine, negatively impacting insulin signalling [ 164 ]. It has been shown that Bacteroidetes and Bifidobacterium contribute to improving mucosal barrier function, resulting in reduced inflammation, improved glucose tolerance, and decreased oxidative stress [ 165 ].…”
Section: The Microbiota Structure and Diet-related Factors In Oestrog...mentioning
confidence: 99%
“…The relative abundance of Firmicutes is positively correlated with insulin sensitivity [ 163 ]. Insulin resistance may result from chronic inflammation, during which pro-inflammatory factors (TNF-α, IL-6, and others) can phosphorylate the insulin receptor substrate, converting it into serine, negatively impacting insulin signalling [ 164 ]. It has been shown that Bacteroidetes and Bifidobacterium contribute to improving mucosal barrier function, resulting in reduced inflammation, improved glucose tolerance, and decreased oxidative stress [ 165 ].…”
Section: The Microbiota Structure and Diet-related Factors In Oestrog...mentioning
confidence: 99%
“…The former can initiate blood coagulation (plasma-free clotting) [ 50 ], whereas the latter can cleave substance P and chemokines [ 51 ]. The bulk of the human microbiota inhabits the gastrointestinal tract (GIT), where it modulates diverse aspects such as insulin signaling, behavior, and allergy [ 52 , 53 , 54 , 55 ]. Similar to EVs that play a role in the host’s intercellular communication, microbiota release outer membrane vesicles (OMVs) that play a role in host–microbiota communication [ 56 ].…”
Section: Biology Of Extracellular Vesiclesmentioning
confidence: 99%
“…The stability, diversity, and composition of the gut microbiota can be impacted by diet, indicating that dietary strategies may be used therapeutically to manipulate it. However, diet-induced changes in the gut microbiota appear to be temporary and may depend on the duration of dietary interventions 93 . Different types of diets can have different effects on the gut microbiota.…”
Section: Dietmentioning
confidence: 99%